Brain weights in adult africans (2017)
Introduction: The average brain weight of adult humans, using Caucasian figures, is said to be between 1300g to 1400g. Few studies have however been done to make actual evaluations of brain weights in adult Africans. This study seeks to examine the weight of brains from people of African descent with respect to variations in sex and age in decades using autopsy specimens. Materials and Methods: Analysis of the weight of brains removed from both male and female adult patients during fresh autopsy of their bodies in our center over a ten year period was done. The study criteria required non-involvement of the central nervous system in the cause of death. The brains were grouped based on age in decades and further grouped into early, middle and late age groups. Descriptive statistical analysis was done using SPSS 20 statistics software. Results: A total of one hundred and sixteen brains were included in the study and the mean brain weight was 1280g with a range between 1015g to 1590g. There was no statistically significant difference in the mean brain weight of the different age groups. The average male brain was heavier than those of females and the difference was statistically significant. Conclusion: The brain weight of adult Africans in our study is similar to that seen in Caucasians. There is no statistically significant difference in the brain weight of adults from early adulthood to the elderly adults. Male adults have statistically heavier brains than the females